Cardiorenal Signaling Pathways in Heart Failure: Good and Bad News - Rosas-Peralta Martin; Palomo-Piñón Silvia; Borrayo Sánchez Gabriela; Pérez Rodríguez Gilberto; Ramón Paniagua-Sierra José (Journal of Hypertension and Cardiology, 2016)
This article reviews heart–kidney signaling in heart failure, contrasting adaptive and maladaptive pathways. It discusses neurohormonal activation, fibrosis, and emerging therapeutic targets.
Keywords: Heart Failure